Tributyltin induces distinct effects on cortical and trabecular bone in female C57Bl/6J mice. Issue 9 (25th March 2018) - Watt, James; Baker, Amelia H.; Meeks, Brett; Pajevic, Paola D.; Morgan, Elise F.; Gerstenfeld, Louis C.; Schlezinger, Jennifer J.
Abstract : The retinoid X receptors (RXR), peroxisome proliferator activated receptor gamma (PPARγ), and liver X receptors (LXR) all have been shown to regulate bone homeostasis. Tributyltin (TBT) is an environmental contaminant that is a dual RXRα/β and PPARγ agonist. TBT induces RXR, PPARγ, and LXR‐mediated gene transcription and suppresses osteoblast differentiation in vitro. Bone marrow multipotent mesenchymal stromal cells derived from female C57BL/6J mice were more sensitive to suppression of osteogenesis by TBT than those derived from male mice. In vivo, oral gavage of 12 week old female, C57Bl/6J mice with 10 mg/kg TBT for 10 weeks resulted in femurs with a smaller cross‐sectional area and thinner cortex. Surprisingly, TBT induced significant increases in trabecular thickness, number, and bone volume fraction. TBT treatment did not change the Rankl : Opg RNA ratio in whole bone, and histological analyses showed that osteoclasts in the trabecular space were minimally reduced. In contrast, expression of cardiotrophin‐1, an osteoblastogenic cytokine secreted by osteoclasts, increased. In primary bone marrow macrophage cultures, TBT marginally inhibited the number of osteoclasts that differentiated, in spite of significantly suppressing expression of osteoclast markers Nfatc1, Acp5, and Ctsk and resorptive activity. TBT induced expression of RXR‐ and LXR‐dependent genes in whole bone and in vitro osteoclast cultures. However, only an RXR antagonist, but not an LXR antagonist, significantly inhibited TBTs ability to suppress osteoclast differentiation. These results suggest that TBT has distinct effects on cortical versus trabecular bone, likely resulting from independent effects on osteoblast and osteoclast differentiation that are mediated through RXR. Abstract : Tributyltin impairs the differentiation of both osteoblasts and osteoclasts, largely via its interaction with the retinoid X receptor. In young adult, female, C57BL/6J mice, tributyltin suppresses periosteal apposition of bone but increases trabecular bone.